Population dynamics of Bagrada hilaris (Brumeister) on Indian mustard under semi arid conditions of Haryana, India (Journal of Oilseed Brassica, 2026)
Population dynamics study of Bagrada hilaris on RH 30 showed that the pest reached its peak population twice in the cropping season, once at the seedling stage, and another at the maturity stage on both early, and late sown crop. The maximum population on early sown crop was observed with its first, and second peak observed on 48th SW, and 12th SW, respectively. While in the late sown crop the peaks in the pest population were noticed on 50th SW, and 17th SW of 2013-14, and 2014-15. The pest population had significant positive correlation with maximum temperature, and sun shine hours on both early, and late sown crops. However, the correlation with minimum temperature was non-significantly positive in early sown crop compared to significant positive correlation in late sown crop. Morning, and evening relative humidity showed highly negative significant correlation with the pest population. Wind speed had a significant negative effect on painted bug population in crop sown early in the season while the effect was positive, and non-significant in late sown crop. All weather parameters contributed to B. hilaris population fluctuation to the extent of 66 to 69, and 46 to 86 per cent during 2013-14, and 2014-15 respectively.